Kinerja keuangan pemerintah provinsi sumatera selatan berdasarkan anggaran pendapatan dan belanja daerah (apbd) tahun 2009-2015 - Welly, Welly; Djuniar, Lis (Jurnal Ekonomi, 2017)
This study aims to determine performance of South Sumatra province. Conclusive type of the study described in descriptive where the variables are financial ratios and government performance. Data used are primary and secondary data which are collected by documentation and interviews. Data analyses used are qualitative and quantitative analysis.Results of the study showed the average of self-sufficiency ratio is 41,21% in low categorized where can be seen from the central government transfers funds revenue is still large, while the potential of PAD is not optimal yet. The average of effectiveness ratio is 96,31% in the effective categorized which can be seen from the realizations to the targets which has not reached 100%. The average ratio of expenditure operation activities is 64,49%, while the capital expenditures is 21,74%, operating expenditure can be seen from particular personnel, goods/services and grants are still high, which grants 2011-2015 expenditure continues increasingly.The average ratio of expenditure management is 94,23% which shows the total of expenditure does not exceed the total income which happened the budget surplus year except 2013. The ratio income and growth of PAD has been in good positive growth except in 2013. The growth of expenditure operation is still high compared to the ratio of capital expenditures growth. Thus the performance of government financial management of South Sumatra province 2009-2015 period is quite well.